Prevalence of bacterial opportunistic infection and associated socio-demographic factors in Human Immunodeficiency Virus infected patients initiated on antiretroviral treatment in Moses Kotane Sub-District, North West Province - Mangali, Ongezwa (My University, 2023)
Background: Human Immunodeficiency Virus (HIV) is a virus that destroys the immune system by weakening the body’s defense (immune cells) against many infections (Anon, 2021). This study was about prevalence of bacterial opportunistic infections and associated socio-demographic factors in human immunodeficiency virus infected patients initiated on antiretroviral treatment in Moses Kotane Sub-District, North West Province. Methodology: The study was a retrospective study design and the data collected included data from 2019-2021. The completed data collection resulted in 1682 records which were collected from five clinics which are Bakubung, Modderkail, Moruleng, Sandfontein and Sefikile. Data was analysed using the STATA statistical software version 12 for Windows (STATA Corporation, College Station, Texas). Results: The prevalence of opportunistic infections in the current study was found to 7.4% which is very low however, this increased with increasing age. Occurrence of these opportunistic infections were significantly associated with age, gender, CD4 count and WHO clinical staging. Tuberculosis remained the number 1 OIs found in these patients and therefore, a significant concern that should be explored is the intervention that can reduce the burden of bacterial opportunistic infection with major focus on Tuberculosis. The current study revealed that there is a paucity of primary data on the contributory factors to opportunistic infections. The study strongly recommends future researchers to do an interventional study which could yield results to address factors influencing high rate of HIV infection amongst youth which will facilitate the development of better public health interventions to reduce the burden of prevalence of opportunistic infection in HIV infected patients. Therefore, it is recommended that clinics in Moses Kotane sub-district be provided with trained staff on screening and diagnose bacterial opportunistic infections early and correct to prevent misdiagnosis.
Thesis (MPH.) -- University of Limpopo, 2023
Keywords: Opportunistic infections; Prevalence; Human immunodeficiency Virus; Antiretroviral treatment; Antiretroviral agents; Aids (Desease) -- South Africa; HIV (Viruses); HIV-positive persons; Opportunistic infections